Conflict over Abkhazia – To Be Continued? - Matsaberidze, David (Journal of Regional Security, 2018)
This paper analyzes the potential for maintaining the post-August War 2008 status quo in Abkhazia and explores possible transformation scenarios of the existing situation. The present study will attempt to investigate the remaining seeds of prospective conflict, as the current reality might contain some potential for the eruption of violence; namely: the construction of the Sochi Olympic complex which irritates Georgians and Circassians as well as portion of Abkhazians; the North Caucasian new policy line, initiated and followed by the central Georgian authorities: and Georgia’s recognition of the Russian Genocide of Circassians in the 19th century, which should become leverage against the Russian Federation in the wider Caucasus region. All of these aspects make up the present security dilemma in the region. It is interesting to see whether changes in the Abkhazian-Georgian and Abkhazian-Russian relations could be expected in the foreseeable future.